2015
DOI: 10.1080/15384101.2015.1006006
|View full text |Cite
|
Sign up to set email alerts
|

Gprc5a-deficiency confers susceptibility to endotoxin-induced acute lung injury via NF-κB pathway

Abstract: Susceptibility to acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) varies greatly among patients in sepsis/septic shock. The genetic and biochemical reasons for the difference are not fully understood. G protein coupled receptor family C group 5 member A (GPRC5A), a retinoic acid target gene, is predominately expressed in the bronchioalveolar epithelium of lung. We hypothesized that Gprc5a is important in controlling the susceptibility to ALI or ARDS. In this study, we examined the suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…Previous studies failed to induce neoplasia and fibrosis in experimental model by silica-exposure, which was probably due to the insensitivity or low response of wild-type mice. Thus, application of Gprc5a −/− mice in this study is important, which ensures that the pathological effects induced by silica exposure was greatly amplified or accelerated since Gprc5a −/− mice are susceptible to lung tumorigenesis [ 15 , 16 , 23 ] and endotoxin-induced lung injury [ 18 ]. In another word, Gprc5a mouse model overcomes the limitation of experiment performed in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies failed to induce neoplasia and fibrosis in experimental model by silica-exposure, which was probably due to the insensitivity or low response of wild-type mice. Thus, application of Gprc5a −/− mice in this study is important, which ensures that the pathological effects induced by silica exposure was greatly amplified or accelerated since Gprc5a −/− mice are susceptible to lung tumorigenesis [ 15 , 16 , 23 ] and endotoxin-induced lung injury [ 18 ]. In another word, Gprc5a mouse model overcomes the limitation of experiment performed in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased M2 macrophages in lungs of silica-exposed Gprc5a −/− mice is consistent with increased tissue damages and fibrogenic response in these tissues. Previously, in the model of endotoxin-induced acute lung injury (ALI), NF-κB target gene expression was greatly activated in lungs from Gprc5a −/− mice compared to wild-type ones following administration of endotoxin, with a peak of activation within 2–24 hour [ 18 ]. However in this study, the mouse model is silica-induced lung injury, in which the samples of lung tissues were collected three months after silica exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gprc5a-knockout (ko) mice developed spontaneous lung adenocarcinoma [26,27], indicating that Gprc5a is a lung tumor suppressor gene. Importantly, tumorigenesis in Gprc5a-ko mouse lung is associated with inflammation along with persistent activation of NF-κB, EGFR, and STAT3 signaling [26][27][28], which resembles the pathological features in human lung cancer. Moreover, GPRC5A is repressed in most of NSCLC and all of chronic obstructive pulmonary disease (COPD) [29].…”
Section: Introductionmentioning
confidence: 90%
“…Here we demonstrated that GPRC5A activates NF-jB pathway in colorectal cancer which is opposite from our previously study that GPRC5A inhibits NF-jB activation in lung injury and tumorigenesis. 20 It suggests that may due to GPRC5A differently regulates the same pathway in tissue type specific manner. As the lung and the digestive tract are the two major tissues with high GPRC5A expression in healthy mouse and humans, it will be interesting to explore the mechanism through which Gprc5a plays dual roles in tumorigenesis in different tissues.…”
Section: Discussionmentioning
confidence: 99%